Reframing educational research : resisting the 'what works' agenda - Farnsworth, Valerie (Routledge, 2013)
Possibilities for the use of research in educational practice are often written off due to the history, politics and interests of the ostensibly separate worlds that researchers and practitioners occupy. However, a more optimistic account highlights the ways these communities share a common need for practice-based theories, which enable them to make sense of a wide range of issues in education, including pedagogy, learning, and educational equity. In applying theory to situated accounts of various educational practices and learning contexts, this book explores mistaken assumptions ab.